Use of oxytocin for the prevention of early embryonic mortality in alpacas - Sánchez, Silvia (2017)
The objective of the present experiment was to test the oxytocin effect on embryonic survival during the luteolysis risk period in post-mating alpacas. Forty-three adult alpacas that were receptive to the male and bearing an ovarian follicle >7 mm of diameter were selected. They were mated with fertile males and the copula lasted for >10 minutes. Ovulation was secured with con 1 ml of GnRH i.m. (Day 0). Within the group of alpacas with a corpus luteum confirmed by trans-rectal echography on day 7, 30 were randomly selected and assigned into two similar groups. One group received 40 IU oxitocin on days 9, 10 and 11 post-mating days distributed in 4 doses of 10 IU every 5 hours. The second group was considered as control. The embryonic survival was evaluated based on sexual receptivity on days 8, 10, 11, 12 and 40 post-mating and confirmed on day 40 by ultrasonography. The oxytocin treated alpacas resulted with embryonic survival of 100% on days 8 and 10, 93.3% on days 11 and 12, and 86.7% on day 40 after mating, whereas non-treated alpacas had 100, 80, 66.7, 46.7 and 46.7%, on days 8, 10, 11, 12 and 40 after mating respectively, with significant differences between groups on days 12 and 40 (p<0.05). In conclusion, exogenous oxytocin reduced the embryonic mortality in alpacas before 40 days of pregnancy.